Peran Pemikiran Heuristik pada Hubungan Persepsi Sosial dengan Munculnya Sikap terhadap Ide Penegakkan Khilafah Islamiyah di Indonesia - Ros Mayasari (Al-Ulum, 2016)
The spread of the idea of application of Khilafah Islamiyah (Islamic Caliphate) emerges zealously over the last few years. This phenomenon occurs especially among the younger generation. Through a quantitative approach, this research examines the theoretical model of the relationship between the need to reject the uncertainty, the social perception of the reality of a society and democratic practices, bias heuristic thinking and the attitude towards the idea of the application of khilafah Islamiyah in Indonesia. Data processed by regression analysis with 245 respondents. Based on the test results of the regression analysis, theoretical models did not fit with the data. Researchers propose a new theoretical model that does not involve variable need of uncertainty avoidance. The ‘bias-heuristic variable’ thinking proves to be an alternative mediator variable in the relationship between social perception of reality of a society, and democratic emergence and attitudes toward the idea of khilafah Islamiyah. For further research, suggested using SEM analysis. Researchers recommended the need to develop and construct the critical thinking among the younger generation, so they become more critical in addressing ideas tend to be radical